Фрaзеологизмы современного турецкого языкa (Вестник КазНУ. Серия Востоковедения, 2017)
Phraseologisms in Turkish, as well as in other languages are used in theintegral value, and don’t change the order of the words. For this reason,they can be used in the language instead of a noun, adjective, adverband verb, and can perform various functions offers. Also phraseologismshave form and semantic features. The article presents a short overview ofphraseologisms Turkish language.